An efficient algorithm for solving the constellation-to-ground region coverage problem based on longitude strip division (Xibei Gongye Daxue Xuebao, 2021)
Aiming at the constellation-to-ground region coverage problem, an efficient solution method called the longitude strip method is proposed. By dividing the ground region into several longitude strips, the latitude range of each strip is computed according to the region. Similarly, concerning the coverage area of the satellite, the latitude range of each strip is also calculated. On this basis, the coverage rate can be obtained by comprehensive statistics. Additionally, the upper and lower bounds for problems of continuous coverage and accumulative coverage are solved. Numerical simulation experiments show the proposed algorithm has higher accuracy and it is also efficient in resolving the ground area with arbitrary shapes.